Perspective: A Framework to Screen Pediatric and Adolescent Hematopoietic Cellular Therapy Patients for Organ Dysfunction: Time for a Multi-Disciplinary and Longitudinal Approach - Ahmad, Ali H.; Mahadeo, Kris M. (Frontiers in Oncology, 2021)
Hematopoietic Cell Transplantation (HCT) is a potentially curative therapy for children and adolescent/young adults (AYA) with high-risk malignancies as well as some non-malignant genetic diseases. However, HCT may be associated with endotheliopathies and/or organ dysfunction that may progress to pediatric multi-organ dysfunction syndrome (pMODS) and require critical care intervention. Discipline specific scoring systems may be used to characterize individual organ dysfunction, but the extent to which they are used to prospectively monitor HCT patients with mild dysfunction is unknown. Further, separate scoring systems may be used to define risk of mortality and inform prognostication among those who require critical care support. Our understanding of the epidemiology, risk factors, morbidity, mortality, required monitoring, optimal prevention strategies and appropriate management of children undergoing HCT who develop organ dysfunction, endotheliopathies and/or progress to pMODS is poor. Discipline-specific registries and clinical studies have described improving outcomes for children undergoing HCT, including those who require critical care support; however, longitudinal studies/prospective registries that capture common data elements among HCT patients with and without organ dysfunction, endotheliopathies and pMODS are needed to facilitate inter-disciplinary collaboration and optimally characterize the risk profiles, define screening and prophylaxis regimens and mitigate toxicity.